Hubungan Pengetahuan dan Perilaku Konsumsi Jajanan dengan Kejadian Diare pada Anak MDTA Al-Hamid di Kecamatan Medan Johor - Meutia Nanda; Annisa Dwi Fahira; Nadiyah Suhailah; Nasika Nurlaila; Yulia Annisyah Siagian (EduInovasi: Journal of Basic Educational Studies, 2023)
In the selection of snacks there are influencing factors, namely external and internal factors. Food contaminated with pathogenic bacteria poses a risk of health problems such as digestive disorders namely diarrhea. This type of research is quantitative research. The sampling technique in this study was carried out using the total sampling method.The population in this study was MDTA Al-Hamid children totaling 30 respondents, which is the total population of children studying at MDTA Al-Hamid Medan Johor District. The results of this study are that there are 20 respondents (76, 9%) who have poor knowledge of snack consumption so that they experience diarrhea and there are 18 respondents (71,5%) who have poor behavior in consuming snacks so that they experience diarrhea. The conclusion of this study is that there is a relationship between knowledge and behavior of snack consumption with the incidence of diarrhea in MDTA Al-Hamid children in Medan Johor District. Keywords: Knowledge, Snack Consumption Behavior, Diarrhea, Children